Volume 5: Turbo Expo 2004, Parts a and B 2004
DOI: 10.1115/gt2004-53612
|View full text |Cite
|
Sign up to set email alerts
|

Multistage Aspects and Unsteady Effects of Stator and Rotor Clocking in an Axial Turbine With Low Aspect Ratio Blading

Abstract: This paper presents the outcome of a recent study in clocking-related flow features and multistage effects occurring in high-pressure turbine blade geometries. The current investigation deals with an experimentally based systematic analysis of the effects of both stator-stator and rotor-rotor clocking. Due to the low aspect ratio of the turbine geometry, the flow field is strongly three-dimensional and is dominated by secondary flow structures. The investigation aims to identify the flow interactions involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…It can be seen that as this vortex region passes the stator leading edge, the turbulence intensity reduces by factor 2. The same effect has been described in more detail in the article by Behr et al [6]. Depending on the relative Fig.…”
Section: Unsteady Rotor Secondary Flowsupporting
confidence: 56%
See 1 more Smart Citation
“…It can be seen that as this vortex region passes the stator leading edge, the turbulence intensity reduces by factor 2. The same effect has been described in more detail in the article by Behr et al [6]. Depending on the relative Fig.…”
Section: Unsteady Rotor Secondary Flowsupporting
confidence: 56%
“…In these studies the circumferential position of the wake of the upstream stator relative to the leading edge of the subsequent stator was mainly held responsible for the effect on efficiency. Contrary effects of clocking positions on different span regions have been found by Behr et al [6], Huber et al [1], Schennach et al [7], and Arnone et al [8]. Consequently, they all suggested to focus more on the three-dimensionality of the flow for explaining clocking phenomena.…”
Section: Introductionmentioning
confidence: 90%
“…These models, which consist of the algebraic Baldwin-Lomax model [16], the one-equation Spalart-Allmaras model [17], and the k−ω model of Wilcox [18], will be compared on the CASCADE. Further descriptions of the solver and its unsteady features as well as turbulence modelling can be found in references [19][20][21][22]. Especially the code's ability to model the unsteady wake correctly in terms of wake depth and diffusion has been the core of interest.…”
Section: Computational Fluid Dynamics-modelling/unsteady Lossesmentioning
confidence: 99%
“…2 Other clocking investigations on the turbines obtained similar results, the maximum efficiency variation influenced by vane clocking varied from 0.3 to 2.0 points. [3][4][5] Besides, vane clocking effect experiment was conducted on compressors. The experiment in NASA's Four-Stage Axial Compressor Facility showed that the impact of stator indexing produced a change of 0.2 points in overall efficiency, but the change was in the band of uncertainty due to manufacturing variations and assembly tolerances.…”
Section: Introductionmentioning
confidence: 99%